Standard Operating Procedure (SOP): trial management - Ayankanmi, T.; Parkes, E.; Rabbi, I.; Kulakow, P.; Iluebbey, P.; Ekanem, U.; Akpotuzor, P.; Olaniyo, E.; Oke, E.; Ogunpaimo, K. (International Institute of Tropical Agriculture, 2024)
Field trials are important in cassava breeding research. Cassava breeders conduct a variety of field trials in the process of developing improved varieties. The results of these trials are used to take informed decisions regarding the variety to release. Good field management can help ensure consistency and repeatability of field trials. Therefore, proper management of field trials is critical for making accurate decisions.